Erratum to Insight into particle production mechanisms via angular correlations of identified particles in pp collisions at √s=7 - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (The European physical journal. C, Particles and fields, 2019)
This document corrects two errors in Eur. Phys. J. C77 (2017) no. 8, 56: the incorrect referencing of Fig. 1 labels in three paragraphs in the results section and a missing acknowledgements section.